Preparing vulnerable social groups for digital education : analysis of Russian inclusive education policies - Zhurukov, Dmitrii (2022)
Digital learning technologies were boosted because of COVID-19 pandemic. The pandemic also made global learning crisis worse, forcing more than 1.5 billion students to stay at home and become online learners. In these circumstances particular attention was paid to the vulnerable social groups and children with disabilities as it was important to sustain their right to education. The context of Russia was chosen due to the low indicators in inclusive education. Therefore, the ways Russian inclusive education policy claims to prepare vulnerable social groups for digital education were studied. To accomplish this objective, Russian policy documents were chosen for the analysis. These documents are Russian Education Policy, Russian Inclusive Education policy, Report on Inclusive education by the Ministry of Education of Moscow Region 2021, Reports on activities and events by the Ministry of Education of Moscow region. These documents were analyses using content analysis. Initial codes were formed, then categories were formed. After that these categories were analyzed based on the relation to the research questions. Findings reveal controversial results. On the one hand, Russian inclusive education policy presents readiness for the inclusive and digital education challenges. Inclusive education definition in the policy document is innovative and correlated with the definitions of the leading academics in the field. Findings also present the readiness to satisfy educational needs of children with disabilities. On the other hand, the scope of the research was limited to the Moscow region which is a benchmarking region in terms of innovation. Therefore, recommendations for the future research are to prepare a study based on the remote areas of the country.